Scoping review of priority setting of research topics for musculoskeletal conditions - Bourne, A.; Johnston, R.; Cyril, S.; Briggs, Andrew; Clavisi, O.; Duque, G.; Harris, I.; Hill, C.; Hiller, C.; Kamper, S.; Latimer, J.; Lawson, A.; et al. (BM J Group, 2018)
Objective Describe research methods used in priority-setting exercises for musculoskeletal conditions and synthesise the priorities identified. Design Scoping review. Setting and population Studies that elicited the research priorities of patients/consumers, clinicians, researchers, policy-makers and/or funders for any musculoskeletal condition were included. Methods and analysis We searched MEDLINE and EMBASE from inception to November 2017 and the James Lind Alliance top 10 priorities, Cochrane Priority Setting Methods Group, and Cochrane Musculoskeletal and Back Groups review priority lists. The reported methods and research topics/questions identified were extracted, and a descriptive synthesis conducted. Results Forty-nine articles fulfilled our inclusion criteria. Methodologies and stakeholders varied widely (26 included a mix of clinicians, consumers and others, 16 included only clinicians, 6 included only consumers or patients and in 1 participants were unclear). Only two (4%) reported any explicit inclusion criteria for priorities. We identified 294 broad research priorities from 37 articles and 246 specific research questions from 17 articles, although only four (24%) of the latter listed questions in an actionable format. Research priorities for osteoarthritis were identified most often (n=7), followed by rheumatoid arthritis (n=4), osteoporosis (n=4) and back pain (n=4). Nearly half of both broad and specific research priorities were focused on treatment interventions (n=116 and 111, respectively), while few were economic (n=8, 2.7% broad and n=1, 0.4% specific), implementation (n=6, 2% broad and n=4, 1.6% specific) or health services and systems research (n=15, 5.1% broad and n=9, 3.7% specific) priorities. Conclusions While many research priority-setting studies in the musculoskeletal field have been performed, methodological limitations and lack of actionable research questions limit their usefulness. Future studies should ensure they conform to good priority-setting practice to ensure that the generated priorities are of maximum value. PROSPERO registration number CRD42017059250.